The development of numeracy problems for junior high school students - Nourma Pramestie Wulandari; Nani Kurniati; Nurul Hikmah; Wahidaturrahmi Wahidaturrahmi (Jurnal Elemen, 2023)
Numeracy has become part of the Minimum Competency Assessment (MCA) used in the National Assessment (NA) since it was established in 2021. However, previous research shows that the numeracy skills of junior high school students are still in the low category. The purpose of this study was to obtain a prototype of a practice book about preparation for dealing with numeracy MCA for junior high school students that were valid, according to experts. This research was development research (R&D) using the Plomp development model, which consists of preliminary research, a prototyping phase, and an assessment phase. At the end of the development stage, there was a formative evaluation to assess the product development's validity by two experts. The instrument used was the validation sheet for the numerical problems book. The results of this study obtained a prototype of the book that contains at least 90 numeracy problems for Junior High School students, which was categorized as valid with an average score of 89 and an excellent classification. The questions used include multiple choice, multiple complex choice, matchmaking, short essay questions, and essay. The dominant portion is in the form of complex multiple-choice questions. This book is suitable for students' preparation for the numeracy MCA.